2012
DOI: 10.1177/0885412211430477
|View full text |Cite
|
Sign up to set email alerts
|

Surveying Models in Urban Land Studies

Abstract: Modern urban regions are highly complex entities. Despite the difficulty of modeling every relevant aspect of an urban region, researchers have produced a rich variety of models dealing with the manifold processes of urban change. This article reviews the models discussed in the literature in order to understand the most important aspects in modeling for urban studies currently. It starts by making a comprehensive review of the sixty-four models mentioned in the literature, and then ''zooms in,'' detailing onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Some articles present their main features and propose a review and a classification (Simmonds et al, 1999;Wegener, 1994;Wegener, 2004;Batty, 2009;Iacono et al, 2008). Others present the existing models in line with different frameworks (Hunt et al, 2005;Silva and Wu, 2012), their application to territories (Feldman et al, 2009;Lautso et al, 2004;Gayda et al, 2005;Sustaincity, 2013) or their historical development (Simmonds and Feldman, 2007). Theoretical issues are also debated, Jin and Wegener (2013) and Anas (2013) for example discuss equilibrium and the evolution towards more dynamic modeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some articles present their main features and propose a review and a classification (Simmonds et al, 1999;Wegener, 1994;Wegener, 2004;Batty, 2009;Iacono et al, 2008). Others present the existing models in line with different frameworks (Hunt et al, 2005;Silva and Wu, 2012), their application to territories (Feldman et al, 2009;Lautso et al, 2004;Gayda et al, 2005;Sustaincity, 2013) or their historical development (Simmonds and Feldman, 2007). Theoretical issues are also debated, Jin and Wegener (2013) and Anas (2013) for example discuss equilibrium and the evolution towards more dynamic modeling.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they are primarily considered as research objects. The gap between lab application and operational use for planning practice is still to be filled (Wegener, 2011;Silva and Wu, 2012;Brömmelstroet and Bertolini, 2008;Aashto, 2007;Nguyen-Luong, 2012). Thus we still need to better understand how LUTIs are currently used, the barriers to their practical use and how they could better inform planning decisions and transport policies in practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was not until the 1990s that these efforts began to thrive (Batty et al 2012;Wu and Silva 2010). A result of these computer models has been a shift from strongly deterministic ways of representing urban systems to more complex adaptive forms that more easily adjust to actual conditions and include more stochastic and heterogeneous characteristics, when dealing with urban land use dynamics (Silva and Wu 2012). However, few simulation models of internal urban land changes that could result the development of creative industries exist.…”
Section: Introductionmentioning
confidence: 99%
“…Schwarz et al (2010) provided a general review of 21 urban models where they found no models were specifically designed for urban shrinkage studies (a process that is marked by the decline of urban population and economic growth). The most recent review was by Silva and Wu (2012) who classified 64 CA urban models based on their level of analysis, the spatio-temporal scale, and tasks performed. These aforementioned reviews focus on the selection of CA models and gave less attention to the selection of factors based on the transition rules.…”
Section: Introductionmentioning
confidence: 99%